Equity in international law - Ahmad, Muhamad Hassan; Eishan Jan, Mohammad Naqib; Masum, Ahmad; Mohamed Nafees, Seeni Mohamed (Sweet & Maxwell, Thomson Reuters, 2022)
Equity is a general principle of law rooted in religious beliefs, ethics, and human reason, and regarded as a source of international law that strengthens other sources of the law or bridges the gaps in treaty law and customary international law. Equity has had been deployed in some circumstances to mitigate the rigour of the law. In some other circumstances, it is applied independently especially when there is no treaty or rule of customary law to apply to solve a legal issue. This means equity plays an important role in the administration of justice not only in municipal legal system, but also in the sphere of international law. Having highlighted the importance of equity, this chapter aims to discuss equity as a source of international law. Since international law can be divided further into two major branches, i.e. ‘public international law’ and ‘private international law’, the chapter discusses how the rules of equity are applicable under both.